Intensified specimen collection to improve tuberculosis diagnosis in children from Rural South Africa, an observational study. - Thomas, Tania A; Heysell, Scott K; Moodley, Prashini; Montreuil, Romualde; Ha, Xia; Friedland, Gerald; Bamber, Sheila A; Moll, Anthony P; Gandhi, Neel; Brant, William E; Sturm, Willem; Shah, Sarita (BMC infectious diseases, 2014)
In drug-resistant TB settings, specimen collection is critical for drug-susceptibility testing (DST). This observational study included multiple specimen types collected from pediatric TB suspects with the aim to determine diagnostic yield and inform clinical practice in children with drug-resistant and drug-susceptible TB.